Digitized HIV/AIDS Treatment Adherence Interventions: A Review of Recent SMS/Texting Mobile Health Applications and Implications for Theory and Practice - Duthely, Lunthita M.; Sanchez-Covarrubias, Alex P. (Frontiers in Communication, 2020)
Background: Mobile health technologies (mHealth) are efficacious along the continuum of HIV/AIDS—from prevention of HIV transmission to those at the highest risk of acquiring infection, to adherence to HIV medical care, for those living with the disease—decreasing the public health burden of the disease. HIV/AIDS is a complex condition, as certain population subgroups are disproportionately affected. Furthermore, barriers experienced at the individual level (e.g. HIV stigma) and at the systems level (i.e. access to care) contribute to these disparities. Low cost, high penetration rates and ease of use mean mHealth SMS/texting solutions hold the biggest promise for curbing the global HIV/AIDS epidemic; yet these technologies have their own challenges. Our primary objective was to assess interventions that promote adherence, which are delivered via SMS/texting, and important design and ethical considerations of these technologies. Specifically, we evaluated the underlying frameworks underpinning intervention design, strategies to safeguard privacy and confidentiality, and measures taken to ensure equity and equitable access across different subgroups of persons living with HIV (PLWH). We also synthesized study outcomes, barriers/facilitators to adherence, and barriers/facilitators of technology to support HIV adherence. Methods: A scoping review methodology was utilized, searching the Medline database for recently published articles (January 2017 to June 2019). Two reviewers independently screened titles and abstracts for relevancy using the following eligibility criteria: a) original research or protocol; b) inclusion of persons living with HIV; b) intervention delivery via SMS/text messaging; and, c) intervention included HIV care adherence. Results: Seven (7) of the 134 articles met full criteria. The great majority (n=6) did not report whether the interventions were developed under established behavioral change models or frameworks. Strategies to address privacy, confidentiality and equity/equitable access were taken in four (n=4) studies. Conclusion: Our mixed methods review determined that privacy and confidentiality remain a concern for PLWH. Provisions to accommodate literacy, infrastructure, technology and other challenges (e.g. access to smartphones and Wifi) are important ethical considerations that guarantee equity and equitable access. Further investigation will determine the contexts within which theoretical models and frameworks remain relevant in the rapidly evolving field of digitized interventions that support adherence.